La rotación de personal relacionado con las compensaciones de los trabajadores de una empresa en sector minero en Perú - Montes Nuñez, Leslie Pierina (2025)
The objective of this research was to analyze the relationship between employee turnover and compensation of the most outstanding employees in the mining company Gold Fields in MUR WY SAC during 2022. A quantitative approach was used with a non-experimental correlational-descriptive design. The sample consisted of 30 employees in a pilot test. To collect data, a survey was administered using a questionnaire validated by expert judgment. The reliability of the instrument was calculated using Cronbach's alpha coefficient (71.0% for 21 items). The results showed that 93.3% of the respondents perceived recognition from their superiors and colleagues, while 76.7% expressed satisfaction with their job. The correlation between turnover and compensation, measured by Spearman's Rho coefficient, was inverse and weak (-0.89%), with a two-tailed significance of 0.642, leading to the acceptance of the null hypothesis. In contrast, the correlation between compensation and the onboarding dimension reached 69.6%, with a significance of 0.000. A low inverse relationship was found between turnover and compensation, suggesting that compensation strategies may not be a critical factor in retaining talent. This highlights the need to review the current compensation approach to improve its impact on retention.